Improving HIV post-exposure prophylaxis rates after pediatric acute sexual assault. (July 2017) - Schilling, Samantha; Deutsch, Stephanie A.; Gieseker, Rebecca; Molnar, Jennifer; Lavelle, Jane M.; Scribano, Philip V.
Abstract: The purpose of our study was to increase the rate of children with appropriate HIV-PEP regimens among those diagnosed with sexual assault in The Children's Hospital of Philadelphia Emergency Department (ED). The outcome measure was the percent of patients receiving correct HIV-PEP. We retrospectively reviewed 97 charts over 31 months to define the baseline rate of children receiving appropriate HIV-PEP regimens (pre QI-implementation period: 2/2012–8/2014). Among children in which HIV-PEP was indicated following sexual assault, 40% received the recommended 28-day course. Root cause analysis indicated prescribing errors accounted for 87% of patients not receiving appropriate HIV-PEP. Process drivers included standardizing care coordination follow-up calls to elicit specific information about HIV-PEP, ED educational initiatives targeted at HIV-PEP prescribing, revision of the clinical pathway to specify indicated duration of HIV-PEP, and revision of the order set to auto-populate the number of days for the HIV-PEP prescription. During the QI-implementation period (9/2014–4/2015), the rate of appropriate HIV-PEP increased to 64% (median 60%) and the average number of days between incorrect HIV-PEP regimens was 24.5. Post QI-implementation (5/2015–3/2016), the rate of appropriate HIV-PEP increased to 84% (median 100%) and the average number of days between incorrect HIV-PEP regimens increased to 78.4. A multifaceted quality improvement process improved the rate of receipt of appropriate HIV-PEP regimens for pediatric victims of sexual assault. Decision support tools are instrumental in sustaining ideal care delivery, but require ongoing evaluation and improvement in order to remain optimally effective.